Development, culture and communication : ties and issues of scientific collaboration in an international, public-organizational and intercultural context : A study of personal relationships : the perspective of Embrapa's employees in Brazil and CIRAD's in France - (:unkn) unknown (My University, 2016)
This study points out the differences between the official and unofficial points of views of two agropastoral research institutions that develop activities in some African countries : the Brazilian Agricultural Research Corporation (Embrapa), based in Brazil, and the French Agricultural Research Centre for International Development (CIRAD), based in France. As for data collection methods, besides a document analysis, this study includes questionaries and valuable semi-structured interviews of member of staff working for both institutions. As for the data analysis part, one adopted the constant comparative method and thematic analysis. The study then followed three thematic axes : 1 - science, progress and development; 2 - culture, quotidian and imaginary and 3 - Organizational, international and intercultural communication. The main question is: nowadays, do relations between Brazil/ France and France/Africa still reproduce the relationships sort of "dominating/ dominated" who was the model in the international relationships between the countries during Modernity ? Not only at a personal level but also in a professional context - say, organizational, scientific and public context. Throughout this study we may conclude that these relationships are far more complex and multi-faced than it can appear when we compare them with stereotypes are based on the dualist framing conveyed by the thought bequeathed on us by Modernity. Some typical traces of this simplistic and reductive views are still alive in the imaginary of social actors consulted as we could check in their own words.
Keywords: African Research